Răspunsuri

Cel mai inteligent răspuns!
2014-11-14T17:51:54+02:00
59-48-5·[66-30:(a-6·8)-32]:2=1
48-5·[66-30:(a-6·8)-32]:2=58
5·[66-30:(a-6·8)-32]:2=10
[66-30:(a-6·8)-32]:2=2
66-30:(a-6·8)-32=4
66-30:(a-6·8)=36
30:(a-6·8)=30
a-6·8=1
a-48=1
a=49
2014-11-14T18:02:18+02:00
59-4x12-5x[66-30:(a-6x8)-32]:2=1                                                                          59-48-5x[66-30:(a-48)-32]:2=1                                                                              48-5x[66-30:(a-48)-32]:2=59-1⇒58                                                                      5x[66-30:(a-48)-32]:2=58-48⇒10                                                                          [66-30:(a-48)-32]:2=10:5⇒2                                                                                [66-30:(a-48)-32]=2x2⇒4                                                                                    66-30:(a-48)=4+32⇒36                                                                                        30:(a-48)=66-36⇒30                                                                                          a-48=30:30⇒1                                                                                                    a-48=1⇔a=48+1⇔a=49
iar a aparut ciudat,deci sa corectez,a-48=30:30=1;a-48=1;a=48+1=49
sper ca ai inteles
da..multumesc :*